Lagrangian coherent structures influence the spatial structure of marine food webs - Jacquelyn M. Veatch; Matthew J. Oliver; Erick Fredj; Hank Statscewich; Kim Bernard; Ashley M. Hann; Grant Voirol; Heidi L. Fuchs; William R. Fraser; Josh T. Kohut (Communications Earth & Environment)
Abstract The patchy distribution of prey in marine environments has a large effect on upper trophic level foraging strategies and distributions. While currents can disperse or concentrate low-motility plankton into patches that reflect the dynamic fluid environments they inhabit, it remains unclear whether surface flows affect motile zooplankton. Here, we used an in-situ optical dataset to detect phytoplankton patches, active acoustics to observe krill, and GPS-tagged penguins to observe three levels of the food web. These data allowed us to investigate whether the local food web overlaps with small-scale surface transport patterns as evidence that dynamic flows structure marine food webs. In Palmer Deep Canyon, Antarctica, we deployed High Frequency radars to measure hourly ocean surface currents, which were subsequently applied to estimate attractive Lagrangian Coherent Structures. We found that phytoplankton patches, Antarctic krill (Euphausia superba), Adélie penguins (Pygoscelis adeliae) and gentoo penguins (Pygoscelis papua) were preferentially located in attracting Lagrangian Coherent Structure features. These results provide evidence that Lagrangian Coherent Structures act as hotspots for prey and associated foraging predators, thus spatially focusing the food web. Results highlight the role of small-scale currents in food web focusing and the importance of transport features in maintaining the Palmer Deep Canyon ecosystem.